Analysis of the effectiveness of usage the “fault tree” method for the prevention of failures in the power economy of food processor - Siryk, Alina; Evtushenko, Olga; Yefisko, Ylia; Ovcharova, Dariya (My University, 2017)
The topic of the paper is the reasons of hazardous events at the power objects of food processing units and their prevention using the “Fault tree” method.
Keywords: кафедра екології та екоменеджменту; labor protection; analysis; dangerous events; modeling; охорона праці; аналіз; небезпечні події; моделювання